Study guides

☆☆

Q: How do you factor 4y2 plus 25y plus 6?

Write your answer...

Submit

Still have questions?

Related questions

4y2 + 25y + 6

(4y + 1)(y + 6)

Assuming the missing signs are pluses, that factors to (4y + 1)(y + 6)

If the missing operational signs are pluses, it factors to (y + 6)(4y + 1)

In the equation x = 4y2 + 6 where x = 42, we need to substitute 42 for x and solve for y. x = 4y2 + 6 42 = 4y2 + 6 42 - 6 = 4y2 + 6 - 6 36 = 4y2 36 / 2 = 4y2 / 2 18 = 4y 18 / 4 = 4y / 4 9 / 2 = y 4 1/2 = y (or 4.5 = y)

If you're looking to factor this expression, then you need to find two values that add up -20, and which multiply to make 4. Unfortunately, no such terms exist, so this expression can not be factored.

10y^2 -12

There are four possibilities depending on the missing operational signs: 4y2 + 2y + 6 factors to 2(2y2 + y + 3) 4y2 + 2y - 6 factors to 2(y - 1)(2y + 3) 4y2 - 2y - 6 factors to 2(y - 1)(2y - 3) 4y2 - 2y + 6 factors to 2(2y2 - y + 3)

(5y - 6)(5y + 6)

6 is a factor

That does not factor neatly.

6(x + 6)(x + 6)

6(13x + 6)

The common factor of 3n2+6 is 3.

x2 + 7x + 6 = (x + 6) (x + 1)

You would factor 2x2 + 7x + 6 into (2x + 3) (x+2)

6(x + 1)(x + 1)

(3x + 1)(x + 6)

(a + 3)( b + 2)

(6 - 5x)(6 - 5x)

(x - 6)(5x - 6)

It is: (x+1)(x+6) when factored

(x + 6)(x + 2)

(X+5)(X+6)

(y+2)(y+3)